Agroforestry in India: Overcoming Challenges to Build a Greener Tomorrow - Ramanjaneyulu, A. V.; Chaitanya, T.; Naik, M. Ramesh; Madhurima, U. (Chronicle of Bioresource Management, 2024)
Agroforestry is an age old concept which combines trees, crops and (or) animals. By cultivating diverse, resilient landscapes, it not only increases agricultural productivity and farmer's income but also helps to achieve food security and climate change mitigation. It enhances biodiversity, and strengthens ecosystem resilience. The present world agricultural scenario seems to be unsustainable and in future also, it is a big challenge to make it sustainable with current agricultural practices. Under such conditions, agroforestry is projected to drive positive changes for sustainable farming globally. It has potential for harmonizing economic growth with ecological responsibility. In the light of this background, we made an attempt to provide synthesized information about multiple benefits besides solutions to address some of the challenges in it’s adoption.